Simbolisme Dan Keindahan Dalam Kesenian Reog Ponorogo: Sebuah Kajian Multidisiplin - Nanda Rochmahningtyas; Trisakti (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Culture is a manifestation of thoughts, customs, and intellect that develop in society. One of the traditional dance arts of Indonesia with strong cultural roots is Reog Ponorogo. The Reog Ponorogo art is a cultural heritage that possesses deep historical and philosophical values. The purpose of this research is to examine the symbolism and beauty of Reog Ponorogo art through a multidisciplinary study. The research method used in this study is descriptive qualitative with a multidisciplinary approach. Multidisciplinarity is an approach in studying the phenomenon of Reog Ponorogo analyzed from the perspectives of anthropology, art, and semiotics related to the symbolism and beauty in that art. The data collection method uses observation sheets and interviews with the tourism office, Reog art activists, and Reog artists. Data analysis is carried out deductively, based on valid theoretical foundations, followed by a description of the data, and concluded with drawing conclusions. The research results show that in Reog Ponorogo art there are symbolism and beauty manifested in the form of movement, costumes, music, and storylines that have been preserved through generations. Every element contained in the Reog Ponorogo performance is very meaningful and becomes a hallmark of a culture that can be integrated into a multidisciplinary study from the perspectives of anthropology, art, and semiotics. The implications of this research impact the preservation of local culture that must be maintained and passed on to future generations.